Development Of Halal Tourism The Land Above The Clouds In North Toraja Regency - Trisno Wardy Putra (LAA MAISYIR: Jurnal Ekonomi Islam, 2021)
Halal tourism is a tourism that prioritizes to provide facilities for visitors that are in accordance with Islamic teachings. However, halal tourism is often misinterpreted by people that accordingly results in misunderstandings among the communities. This study aims to explain the development of halal tourism in the Land above the Cloud, pong torra’ in North Toraja Regency. The method employed was qualitative method, which specifically used descriptive analytical approach to holistically understand the phenomenon that occurred in the area being investigated. The result revealed that the development of halal tourism in North Toraja Regency still became polemics which was accordingly rejected as the immediate impact of the lack of socialization to the community. In addition, the provision of Islamic religious facilities and infrastructure prepared by the manager had not been maximized. Based on the result of this study, it can be concluded that intense communication is highly required between the government and the community to avoid the misconception about halal tourism. Furthermore, it is necessary to improve the facilities and infrastructure in order to attract more Muslim tourists to visit.